How immigrant children affect the academic achievement of native Dutch children - Asako Ohinata; Jan C. van Ours (Institute for the Study of Labor (IZA), 2011)
In this paper, we analyze how the share of immigrant children in the classroom affects the educational attainment of native Dutch children. Our analysis uses data from various sources, which allow us to characterize educational attainment in terms of reading literacy, mathematical skills and science skills. We do not find strong evidence of negative spill-over effects from immigrant children to native Dutch children. Immigrant children themselves experience negative language spill-over effects from a high share of immigrant children in the classroom but no spill-over effects on maths and science skills.
urn:nbn:de:101:1-201201113729
Keywords: I21; J15; 330; immigrant children; peer effects; educational attainment; Kinder; Migranten; Soziale Gruppe; Bildungsverhalten; Schule; Niederlande